Analisis Laporan Keuangan Debitur Terhadap Keputusan Pemberian Kredit di PT. Bank Perkreditan Rakyat (BPR) Payung Negeri Bestari (PNB) Pekanbaru - Fristy, Anne Monika; K, Kardi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study was to determine whether the analysis of the debtor's financial statements on the decision to grant credit was in accordance with the standards and criteria and procedures for granting credit at PT. BPR Payung Negeri Bestari (PNB) Pekanbaru, reviewed from a financial aspect. For banks, credit is the main source of income, as well as the largest source of operational risk in the company. The bank in distributing its funds, the bank first analyzes the debtor's eligibility for the last three periods. The purpose is to prevent losses or bad debts. debtor performance to find out whether it is worthy of receiving credit. The author uses a descriptive analysis method by comparing, in the form of financial statements for the last three periods. Then the author uses Quantitative analysis, namely financial ratio analysis. The results of the study showed that of the three debtors, only two debtors had all their financial ratios in accordance with the bank's ratio standards and were said to be safe in their credit. Then debtor one according to the results of the researcher's analysis had two financial ratios that did not comply with the bank's ratio standards and were said to be less safe in their credit. Although the decision from the bank was worthy of getting credit. Maybe the bank in making credit decisions is not only seen from the financial aspects of the debtor, but the bank also looks at other aspects. In analyzing, banks should continue to uphold the principles of prudence in providing credit so that the decisions taken will be appropriate and professional.